2011
DOI: 10.1007/s00704-011-0413-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spatial and temporal characteristics of rainfall in Malawi: a case of data scarce region

Abstract: This paper presents the methods, procedure and results in studying spatial and temporal characteristics of rainfall in Malawi, a data scarce region, between 1960 and 2006. Rainfall variables and indicators from rainfall readings at 42 stations in Malawi, excluding Lake Malawi, were analysed at monthly, seasonal and annual scales. In the study, the data were firstly subjected to quality checks through the cumulative deviations test and the standard normal homogeneity test. Spatial rainfall variability was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 59 publications
7
128
1
Order By: Relevance
“…As described in the literature (Ceballos et al 2004;Nel2009;Ngongondo et al 2011), PCI values below 10 indicate a uniform monthly rainfall distribution in the year, whereas values from 11 to 20 denote seasonality in rainfall distribution. Values above 20 correspond to climates with substantial monthly variability in rainfall amounts (Nel 2009 and references therein).…”
Section: Rainfall Mean Characteristicsmentioning
confidence: 96%
See 4 more Smart Citations
“…As described in the literature (Ceballos et al 2004;Nel2009;Ngongondo et al 2011), PCI values below 10 indicate a uniform monthly rainfall distribution in the year, whereas values from 11 to 20 denote seasonality in rainfall distribution. Values above 20 correspond to climates with substantial monthly variability in rainfall amounts (Nel 2009 and references therein).…”
Section: Rainfall Mean Characteristicsmentioning
confidence: 96%
“…A preliminary examination of monthly totals showed that a number of monthly records had missing values. This is a challenge to which a number of studies (Türkeş 1996;Sahin and Cigizoglu 2010;Ngongondo et al 2011) have applied different techniques to make rainfall data set complete. In this study, we applied the linear regression method.…”
Section: Missing Value Interpolationmentioning
confidence: 99%
See 3 more Smart Citations